Nutritional status and laboratory characteristics of nephrotic syndrome in children undergoing steroid and non-steroid therapy at Dr. Zainoel Abidin Hospital, Banda Aceh - Syafruddin Haris; Fahrul Riza; T. M. Thaib; Anidar Anidar; Bakhtiar Thaib; Nora Sovira (AcTion: Aceh Nutrition Journal, 2025)
Nephrotic syndrome (NS) is a clinical condition characterized by massive proteinuria, hypoalbuminemia, edema, and hypercholesterolemia. Frequently relapsing NS, steroid-dependent NS, and steroid-resistant NS are categorized as problematic owing to treatment difficulties. These patients require prolonged high-dose steroid therapy or immunosuppressants, resulting in significant side effects. This study evaluated the nutritional status and laboratory characteristics of NS in children undergoing steroid and non-steroid therapies. This study is the first to assess the nutritional status and laboratory characteristics of children with difficult-to-treat NS who received steroid and non-steroid therapy at RSUDZA Banda Aceh. A cross-sectional study was conducted at the outpatient clinic and pediatric ward of Dr. Zainoel Abidin General Hospital, Banda Aceh, in 2019, which was a limitation because it was conducted during the Covid-19 pandemic so that the number of research subjects was limited, which could have caused bias in the study. Statistical analyses included the chi-square test or Fisher’s exact test for categorical variables and the independent sample t-test or Mann-Whitney test for numerical variables, with a 95% significance level (p < 0,05). A total of 60 children aged 2–18 years participated in this study, with 29 receiving steroid therapy and 31 receiving non-steroid therapy. Urine protein levels and relapse incidence differed significantly between the groups (p < 0,001). However, the serum albumin, urea, creatinine, calcium, and total cholesterol levels were not significantly different. No significant differences were observed in the laboratory characteristics between the steroid and non-steroid therapy groups. However, the non-steroid group exhibited a better urine protein status and fewer relapses, indicating potential therapeutic advantages.